2021
DOI: 10.1017/jfm.2021.366
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of supersonic twin-jet coupling using spatial linear stability analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…In recent years, the feedback has been attributed to guided jet modes (e.g. Tam & Hu 1989; Nogueira & Edgington-Mitchell 2021), though the physics of these modes is not yet clear. Given the importance of LSS timing and organization to the screech process as well as the employed control technique, determining the appropriate method for scaling the relevant frequency is crucial.…”
Section: Baseline Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the feedback has been attributed to guided jet modes (e.g. Tam & Hu 1989; Nogueira & Edgington-Mitchell 2021), though the physics of these modes is not yet clear. Given the importance of LSS timing and organization to the screech process as well as the employed control technique, determining the appropriate method for scaling the relevant frequency is crucial.…”
Section: Baseline Resultsmentioning
confidence: 99%
“…More recently, it has been suggested that the feedback waves for screech may be due to a guided jet mode (Tam & Hu 1989; Edgington-Mitchell et al. 2018; Nogueira & Edgington-Mitchell 2021). Zaman et al.…”
Section: Baseline Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2018; Gojon, Bogey & Mihaescu 2018; Mancinelli et al. 2019) and in supersonic twin jets (Nogueira & Edgington-Mitchell 2021). In these cases, strong aeroacoustic resonance processes, which can be isolated using the proper orthogonal decomposition method for instance (Edgington-Mitchell et al.…”
Section: Introductionmentioning
confidence: 99%
“…2018), as well as numerically for ideally expanded (Bogey & Gojon 2017) and shock-containing (Gojon & Bogey 2017) impinging jets. Further, in a consideration of twin jets, which can exhibit a range of different coupling symmetries, it has been demonstrated that only those symmetries where the G-JM is propagative are observed in experimental data (Nogueira & Edgington-Mitchell 2021). Thus the suggestion of Shen & Tam (2002) that the G-JM might be a component of jet screech appears to have been prescient; however, they suggested that it might be active only in certain mode stages, while the present evidence suggests that the G-JM is actually the upstream component of all screech stages (Nogueira et al.…”
Section: Introductionmentioning
confidence: 99%